Pernikahan dalam Islam Membina Keluarga yang Sakinah Mawaddah dan Rahmah - Nabil Hukama Zulhaiba Arjani; Dominick Hoki Pinky; Adisty Puji Nurjayanti; Hanifah Hafshoh; Wismanto Wismanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Marriage in Islam is a sacred agreement, with the aim of worshiping Allah, but also a concept that embraces religious, moral and social values. And it is valid if it meets the terms and conditions. Where there are 5 laws in marriage, namely obligatory, sunnah, makruh, permissible and haram. The aim of this research aims to discuss marriage as well as the promise of purity carried out by men and women who want to continue a halal relationship, and perfect part of their faith. This research uses a qualitative method with a literature study approach, analyzing various sources such as books, magazines, offline and online articles or the latest journals, all data found from reading sources is then expressed in qualitative descriptive form. The results of this research show the problem of marriage in Islam in building a family that is sakinah mawaddah and rahmah. One of Allah's instructions in Islamic law is that He commands marriage and forbids adultery. Isalam has provided a clear concept regarding the procedure or process of a marriage which is based on the Al-Quran and the authentic Sunnah. Therefore, in this journal the author explores the meaning of marriage, the legal basis, conditions, harmony and wisdom of the law of marriage.